Effects of multicycle-run training on triathlete performance - Hue, O.; Valluet, A.; Blonc, S.; Hertogh, C. (Research Quarterly for Exercise and Sport, 2002)
The purpose of this study was to determine the effect of triathlon training using multiple, short cycle-run sequences (multicycle-run training) on cycle-run performance. Twelve competitive triathletes, randomized into two groups, underwent multicycle-run training or normal training for 6 weeks. During this period, baseline training remained the same for both groups, and only the high-intensity component differed. The differentiated exercises were performed at or above 100% maximal aerobic velocity. The improvements in overall cycle-run performance were similar (3.3 +/- 1.4 % and 6.1 +/- 1.7% rise in Performance in multicycle-run and normal training, respectively). However, the improvement in performance was significantly greater for the multicycle-run training (-11.2 +/- 6.8 s versus -1.2 +/- 7.7 s for multicycle-run training and normal training, respectively) during both the cycle-run change and thefirst 333-m lap, which together are termed the cycle-run transition. We concluded that 6 weeks of multicycle-run training did not induce greater improvement in cycle-run performance than did normal training in competitive triathletes. However, it did induce significant improvement in the cycle-run transition. This finding indicates that multicycle-run training may help competitive triathletes to develop greater skill and better physiological adaptations during this critical transition period of the triathlon race.